Analisa Hubungan antara Faktor-Faktor yang Mempengaruhi Perilaku Pembelian Susu Kambing di Wilayah Bogor - Kisworo, Arif Nindyo; Handayani, Kusuma Sri (Jurnal Aplikasi Manajemen, 2014)
This study aimed to analyze the market segmentation of goat milk in the region of Bogor, as well as examine consumer characteristics and beneficial aspects that affecting consumer's interest in consuming goat milk in order to make as the basis data in formulating the marketing strategies of goat's milk. This study started to conduct in December 2009 and ends in March 2010 in Bogor and its surrounding areas. The subjects of this study are dairy goat breeders, agents and retailers of goat's milk, and individuals goat milk consumers. Data analysis was performed by descriptive analysis, Structural Equation Modeling (SEM) and cluster analysis. The results of this study shows that consumers'purchasing interest is directly affected by the social and psychological factors of consumer, and does not influenced by personal factors and consumer subculture. Consumer factually purchasing is directly affected by the personal factors (education level and occupation) and consumer purchase interest; indirectly affected by social and psychological factors, but does not influenced by subcultural factors of the consumer. Consumer market segmentation based on the terms of the benefits of goat milk products expected, are consumers who care about the health, productive consumer which age of 21 to 60 years, relatively high educated and working as private employees, state employees and civil servants as well as derived from the Javanese and Sundanese. Goat milk consumers in the area of Bogor are not dominated by Arabs and Chinese ethnic groups, but mainly from the Sundanese and Javanese. The improvement of the image of goat's milk as a health drink can be done by promoting throughadvertising, distribution, and improving customer service.